2003
DOI: 10.1213/01.ane.0000066310.49139.2a
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Dexamethasone, Ondansetron, and Dexamethasone plus Ondansetron as Prophylactic Antiemetic and Antipruritic Therapy in Patients Receiving Intrathecal Morphine for Major Orthopedic Surgery

Abstract: Postoperative nausea and vomiting (PONV) and pruritus are common side effects after spinal opioid administration. In this study, dexamethasone 8 mg plus ondansetron 4 mg was as effective as ondansetron 8 mg. The administration of dexamethasone alone was associated with a frequent incidence of PONV, demonstrating a lack of efficacy. This has important cost implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
3
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 20 publications
3
34
3
5
Order By: Relevance
“…Activation of opioid receptor and 5-HT3 receptors in the dorsal part of spinal cord and the nucleus of the spinal tract of the trigeminal nerve in the medulla by neuraxial opioid administration or by circulating oestrogen in the parturients result into neuraxial opioid-induced pruritus. 21 In this study, the incidence of puritus and nausea are similar in both the groups because of prophylactic administration of 8 mg ondansetron 30 minutes before surgery. Intrathecal morphine is safe for new born baby as the APGAR score in 1 minute and 5 minutes are similar and within normal limits in both the groups because of very minimal systemic absorption of intrathecal morphine.…”
supporting
confidence: 48%
“…Activation of opioid receptor and 5-HT3 receptors in the dorsal part of spinal cord and the nucleus of the spinal tract of the trigeminal nerve in the medulla by neuraxial opioid administration or by circulating oestrogen in the parturients result into neuraxial opioid-induced pruritus. 21 In this study, the incidence of puritus and nausea are similar in both the groups because of prophylactic administration of 8 mg ondansetron 30 minutes before surgery. Intrathecal morphine is safe for new born baby as the APGAR score in 1 minute and 5 minutes are similar and within normal limits in both the groups because of very minimal systemic absorption of intrathecal morphine.…”
supporting
confidence: 48%
“…Activation of 5-HT 3 receptors in CTZ by cephalad migration of morphine in cerebrospinal fluid appears to be one of the mechanisms of intrathecal morphine-related PONV [15]. Although all the 5-HT 3 receptor antagonists have been found equally anti-emetic and are effective for the prevention of PONV after general anaesthesia, their effects in neuroaxial opioidrelated PONV are inconclusive [16]. Pitkanen and colleagues demonstrated that neither 8 mg ondansetron twice daily nor 5 mg tropisetron once daily, intravenously, was effective in preventing PONV after 0.3 mg intrathecal morphine [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative nausea and vomiting (PONV) occurs frequently, with a reported incidence of up to 74% and lasting up to 24 h [1]. Serotonin (5-HT 3 ) receptor antagonists have been used as anti-emetics to prevent or to treat nausea and vomiting induced by intrathecal morphine [2][3][4][5][6]. Mirtazapine is a new antidepressant that selectively blocks postsynaptic 5-HT 2 and 5-HT 3 receptors [7].…”
mentioning
confidence: 99%
“…However, this may be attributable to the difference in the mechanism of emesis induced by drugs administered via the intrathecal route compared with epidural drugs. Szarvaset al [21] found that coadministration of intravenous dexamethasone and ondansetron for prevention of PONV in patients undergoing major orthopedic surgery using spinal morphine was no more effective than the standard antiemetic therapy of ondansetron alone. Similarly, Nortcliffe et al [4] reported that intravenous cyclizine administered immediately after cesarean delivery significantly decreased the incidence and severity of nausea and vomiting and the need for rescue antiemetic therapy compared with intravenous dexamethasone or placebo.…”
Section: Discussionmentioning
confidence: 99%